Timing and temporal trends of influenza and pertussis vaccinations during pregnancy in three Australian jurisdictions: The Links2HealthierBubs population‐based linked cohort study, 2012–2017. (13th June 2022) - Mchugh, Lisa; Van Buynder, Paul; Sarna, Mohinder; Andrews, Ross M.; Moore, Hannah C.; Binks, Michael J.; Pereira, Gavin; Blyth, Christopher C.; Lust, Karin; Foo, Damien; Regan, Annette K.
Abstract : Background: Antenatal inactivated influenza (IIV) and pertussis‐containing vaccines (dTpa) offer protection against severe respiratory infections for pregnant women and infants <6 months of age. Both vaccines are recommended in pregnancy; however, little is known about temporal or jurisdictional trends and predictors of uptake. Aims: To identify gaps and predictors of IIV and/or dTpa vaccinations in Australian pregnancies from 2012 to 2017. Materials and Methods: We conducted a probabilistically linked, multi‐jurisdictional population‐based cohort study, drawing from perinatal data collections and immunisation databases. We used a generalised linear mixed model with a random effect term to account for clustering of multiple pregnancies within mothers, to calculate vaccination uptake, and identify predictors of uptake by maternal demographic, pregnancy, and health characteristics. Results: Of 591 868 unique pregnancies, IIV uptake was 15%, dTpa 27% and 12% received both vaccines. Pertussis vaccinations in First Nations pregnancies were 20% lower than non‐Indigenous pregnancies; dTpa was strongly associated with IIV uptake (risk ratio (RR): 8.60, 95% CI 8.48–8.73). This trend was temporally and jurisdictionally consistent. First Nations women were more likely to have had IIV in pregnancy before the introduction of dTpa in the pregnancy program: (RR: 1.48, 95% CI 1.40–1.57), but less likely after dTpa implementation (RR: 0.78, 95% CI 0.76–0.80). Conclusions: Inequity in vaccine uptake between First Nations and non‐Indigenous pregnancies, and dismal rates of vaccination in pregnancy overall need urgent review, particularly before the next influenza pandemic or pertussis outbreak. If antenatal dTpa is driving IIV uptake, changes in antenatal healthcare practices are needed to ensure vaccines are offered equitably and optimally to protect against infection.